The impact of corporate social responsibility, energy consumption, energy import and usages and carbon emission on sustainable economic development: Evidence from ASEAN countries - Tien-Dung Nguyen; Quang Thanh Ngo (Contemporary Economics, 2022)
Recently, sustainable economic development has become a global requirement and also has gained the attention of recent studies and policymakers nowadays. Thus, the present study has examined the impact of corporate social responsibility (CSR) along with renewable energy consumption, energy usage and import and carbon emission on the sustainable economic development of the Association of South-East Asian Nations (ASEAN). This study has adopted the quantitative method of data collection and used secondary data collection sources. The data has been extracted from the world development indicators (WDI) and reports published on the sustainability of the countries. This study has gathered the post-financial crisis data from 2011 to 2020. This study has executed the robust standard error and fixed effect model (FEM) to examine the relationships among variables. The results revealed that CSR, renewable energy consumption, and energy usage and import have a positive and significant associations with the sustainable economic development of the ASEAN countries. The outcomes also exposed that carbon emission has a negative but significant nexus with the sustainable economic development of the ASEAN countries. These outcomes provide the guidelines to the regulation-making authorities while formulating policies related to sustainable economic development in accordance with CSR and energy policies.
Keywords: O11; Q43; D22; C33; 330; corporate social responsibility; renewable energy consumption; energy usage; energy import; carbon emission; sustainable economic development